The influences of PLA into PMMA on crystallinity and thermal properties enhancement-based hybrid polymer in gel properties - Norfatihah, Mazuki; Nagao, Y.; M. Z., Kufian; A. S., Samsudin (Elsevier Ltd, 2022)
Polymer blends have been intensively studied because of their theoretical and practical importance in different variety application field. In the present work, the development on hybrid gel polymer based poly(methylmethacrylate) (PMMA) blended with biodegradable polymer namely poly(lactic acid) (PLA) as a host polymer in polymer electrolytes application have been successfully prepared. The effect of PLA in PMMA as hybrid polymer was investigated for their structural properties via fourier transform infrared (FTIR), x-ray diffraction (XRD) and differential scanning calorimetry (DSC). FTIR analysis shown that the interaction between PMMA and PLA has occurred via dipole-dipole forces. XRD analysis revealed the increment of amorphous phase when PLA was added into PMMA. Decreased in Tg value upon addition of PLA into PMMA indicate that the flexibility of the polymer backbone, thus enhanced the amorphous behaviour of hybrid gel polymer. These findings shown that the present hybrid polymer shown favourable properties to be used as host polymer for polymer electrolytes application.